Economic assessment and optimization of the Selexol process with novel additives. (November 2015) - Im, Dasom; Roh, Kosan; Kim, Junhan; Eom, Yongseok; Lee, Jay H.
Highlights: Economic feasibility of the Selexol process employing three solvent additives is examined. Triacetin as the solvent additive showed the best performance in terms of operating and equipment costs. The optimal lean solvent temperature was found at various CO2 capture rates. Abstract: Despite the rising concern with climate change, carbon capture is yet to be implemented widely in industry due to its high cost. In this study, three candidate compounds, dimethyl carbonate (DMC), diethyl carbonate (DEC), and triacetin (TAT), are considered as additives for the solvent, Dimethyl Ethers of Polyethylene Glycol (DEPG), to improve the economics of the Selexol process. To discuss their economic feasibility, the 1-stage Selexol process employing each solvent additive is developed, and their operating and equipment costs are compared with those of the reference process (without the additive). The process employing the TAT additive is shown to be competitive with the reference process in terms of both operating and equipment costs, but DMC and DEC showed a serious problem in terms of solvent loss. For reducing the operating cost and CO2 capture cost further, the lean solvent temperature of the Selexol process with the TAT solvent additive is optimized at various CO2 capture rates.